Collaborative E-Learning Model Development for Increase Quality Learning in Vocational School - Didi Kurnaedi; Setyawan Widyarto (bit-Tech, 2024)
The creation of a collaborative e-learning model is an urgent need, especially in Tangerang, to improve the quality of education in Vocational High Schools (SMK). Vocational learning requires integration between theory and practice, but traditional e-learning systems have not been able to meet this need. This study aims to develop a personal collaborative e-learning model that combines interactive support-based learning, context-based collaboration, and practice-oriented learning. The research methodology uses the ADDIE model  with a Research and Development  approach. The subjects of the study involved 22 teachers and 375 students from various vocational schools in Tangerang. Data collection was carried out through questionnaires, observations, interviews, and test results, with three trial classes for one semester. The results showed that the collaborative e-learning paradigm significantly increased student engagement, learning quality, and learning outcomes. As many as 82% of students felt their learning experience was more meaningful than the previous e-learning method, while 85% of students actively participated in discussion forums and collaboration. The test results showed an average increase in scores of 15%. Teachers also assessed that this strategy supports the development of students' practical skills and facilitates project-based learning. Satisfaction evaluations showed that 80% of students felt more satisfied with the learning experience using this collaborative model. The collaborative e-learning model developed is not only relevant for learning in SMK Tangerang, but also has the potential to improve the standard of vocational education in Indonesia. Training and infrastructure support are needed to ensure the sustainability of the implementation of this model.